Analisis Akuntansi Wakaf Pada Entitas ABC - Imam Baihaqi; Imroatul Hasanah; Zami Salsabela; Muhammad Syarofi; Yuan Gang Tsai (Penerbit Hellow Pustaka, 2025)
Waqf accounting is a field that focuses on the management and reporting of waqf assets characterized by the application of Islamic law. In general, waqf is a legal act carried out by a person (wakif) to endow part of his assets for the benefit of worship and community welfare, either for a certain period of time or forever. The analysis of waqf accounting in the ABC entity aims to evaluate the application of PSAK 112 in the management and reporting of waqf assets. This research method uses qualitative research methods such as class action, case studies, and others. Waqf assets can be in the form of movable and immovable objects. This recognition must comply with special rules regarding the transfer of control over economic interests in assets.